The Ethical Dilemmas of Bilbo Baggins: Utilitarianism in J.R.R. Tolkien’s The Hobbit - Hazel D Arunodaya; Dr. J. Pinky Diana Evelyn (ILN Journal: Indian Literary Narratives, 2025)
Mankind is, at its most primal form, predatory. If one were to take a look back at humanity’s past, one would be confronted with the fact that our ancestors were not very different in comparison to the wildlife around them. They fought and killed for survival. They were territorial and feral. This can be justified by the fact that the environment in which they had to survive demanded that they be savage and untamed. The unsympathetic nature of their surroundings did not let them let go of their wild nature even for a day. As mankind evolved and civilisations cropped up, their feral nature did not completely go away. It was masked by a façade of civility and humane values. However, the façade could easily be torn away at the slightest provocation. Even after civilisations were established and humanity, with the help of technology, progressed in leaps and bounds, Man still went to war because of his inability to share natural resources, lands etc. In wars, the common individual’s life ceases to hold meaning and becomes part of one collective whole. Whole populations suffered for no good reason. Thus, the true mark of a culturally well – developed society is sharing. This is because sharing stems from the heart, contributes to the development of a society and ensures that no one is hurt in the process. No man is obligated to share his resources with his neighbour. However, when a man decides to help his neighbour just for the sake of helping, with no selfish intentions, one can say Utopia has been established. In short, a Utilitarian society is a Utopian society. Utilitarianism is a concept which was first introduced by Jeremy Bentham and it was further developed by John Stuart Mill. Mill’s Utilitarianism posits that the action which causes the greater good for the greatest number of people must be considered as the right action. J.R.R. Tolkien is a British novelist who is well known for his Lord of the Rings series. His works explores the ramifications of being obsessed with oneself with no care for others, the harmful consequences of greed and avarice and how a humane society can be birthed with the help of selfless individuals aiming for the greater good. This research paper aims to study instances of Utilitarianism exhibited by Bilbo Baggins in Tolkien’s novel The Hobbit and prove that Utilitarianism is a just model to be followed to establish an ideal society.